The Influence Of Achievement Motivation, Teaching And Learning Style Towards Textile Learning Outcomes - Endang Triastuti; Putu Sudira (Universitas Negeri Makassar, 2019)
This study aims at revealing the influence of: (1) teaching style towards textile learning outcomes, (2) learning styles towards textile learning outcomes, (3) the effect of from teaching style, learning style, and achievement motivation towards textile learning outcomes, (4) the significance of teaching style, learning style and, achievement motivation towards textile learning outcomes for individual or group. This research can be categorized as quantitative study with a correlational model. The data analysis used multiple regression analysis techniques. The results of the study showed that (1) there is a positive and significant influence of teaching style towards textile learning outcomes, (2) there is a positive and significant influence of learning styles towards textile learning outcomes, (3) there is a positive and significant influence from teaching style, learning style, and achievement motivation towards Textile learning outcomes, (4) the influence of teaching style, learning style and achievement motivation were 26.6% and the rest was coming from other factors.